Scientific evidence for the management of dentin caries lesions in pediatric dentistry: A systematic review and network meta-analysis. - Tamara Kerber Tedesco; Thais Gimenez; Isabela Floriano; Anelise Fernandes Montagner; Lucila Basto Camargo; Ana Flávia Bissoto Calvo; Susana Morimoto; Daniela Prócida Raggio (PLoS ONE)
Background A systematic quantitative evaluation of the available evidence of the treatment for caries lesions in primary teeth that considers how different caries progressions lead to the need for distinct interventions might provide additional useful information for clinical evidence-based decision making. The aim of this systematic review and network meta-analysis was to verify the effect of the treatments on caries lesion arrestment (CLA) or the success rate (SR) of dentin caries lesion treatments in the primary teeth. Methods A search was conducted using the MEDLINE/PubMed, Web of Science and Scopus databases through December 2017. The primary search terms used in combination were primary teeth, caries lesion and restoration. The grey literature was also screened, as were the reference lists of eligible studies. A search of prospective studies with at least 12 months of follow up that compared different techniques was performed. The exclusion criteria were the absence of a comparison group; no evaluation of different restorative techniques; the evaluation of other outcomes unrelated to this review; and the recruitment of specific patient. The risk of bias was evaluated by the tools: the Cochrane Handbook for Systematic Reviews of Interventions and ROBINS-I. A network meta-analyses and meta-analyses were conducted considering CLA or SR as outcomes according to the surface involved and the depth of progression. Results Of the 1671 potentially eligible studies, 15 were included. For occlusal surfaces, only two studies presented data regarding the outer half of the dentin, with conventional restorative treatment (CRT) using composite resin showing superior results; five studies presented data regarding the depth of caries lesions, and CRT with compomer resulted in the best results. Seven studies considered occlusoproximal surfaces, and the Hall technique showed the best SR among the evaluated treatments. Finally, two annual applications of silver diamine fluoride showed the best nonrestorative approach to arrest caries lesions on occlusal and smooth surfaces. Discussion/conclusions The treatments for dentin caries lesions in primary teeth depend on the depth of progression and the surface involved. However, few of the included studies provided evidence to strongly recommend the best treatment option. Other Funding: FAPESP; Systematic review registration number-PROSPERO CRD42016037784.